Pengaruh Afiliasi Dalam Pemasaran Digital Dan DampaknyaTerhadap Penjualan Pada PT Shopee International Indonesia - Syahzanan Sahilah; Iwan Sukoco; Nurillah Jamil Achmawati Novel; Cecep Safa’atul Barkah (LPPM Universitas Multi Data Palembang, 2023)
This research investigates the impact of affiliate marketing in digital marketing and its influence on salesat PT Shopee International Indonesia. The aim of this study is to explore the role of affiliate strategies in the contextof digital marketing and how these strategies contribute to sales growth. The research adopts a qualitative approach, utilizing literature review, interviews with Shopee users, and sales data from PT Shopee InternationalIndonesia. The findings of this study reveal the significance of the affiliate’s role in driving sales and highlight itspotential as an effective marketing tool in the digital era. The research concludes by emphasizing the importance ofimplementing affiliate strategies in digital marketing campaigns to enhance sales performance.